2022
DOI: 10.1002/tpg2.20281
|View full text |Cite
|
Sign up to set email alerts
|

The soybean ubiquitin‐proteasome system: Current knowledge and future perspective

Abstract: Increasing soybean [Glycine max (L.) Merr.] yield has become a worldwide scientific problem in the world. Many studies have shown that ubiquitination plays a key role in stress response and yield formation. In the UniProtKB database, 2,429 ubiquitinrelated proteins were predicted in soybean, however, <20 were studied. One key way to address this lack of progress in increasing soybean yield will be a deeper understanding of the ubiquitin-proteasome system (UPS) in soybean. In this review, we summarized the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 141 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Seed size and weight are closely related to oil content in soybean [ 11 , 29 ]. Multiple signalling pathways are involved in the regulation of seed size, including photosynthesis, carbon metabolism, histone methylation, hormone signalling pathway, ubiquitin protease pathway and MKKK pathway [ 3 , 27 , 39 , 40 ]. These pathways regulate seed size by controlling embryo and endosperm development and the proliferation and growth of seed coat or hull cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed size and weight are closely related to oil content in soybean [ 11 , 29 ]. Multiple signalling pathways are involved in the regulation of seed size, including photosynthesis, carbon metabolism, histone methylation, hormone signalling pathway, ubiquitin protease pathway and MKKK pathway [ 3 , 27 , 39 , 40 ]. These pathways regulate seed size by controlling embryo and endosperm development and the proliferation and growth of seed coat or hull cells.…”
Section: Discussionmentioning
confidence: 99%
“…Merr.) is one of the most economically important protein and oil seed crops [ 1 3 ]. At present, the main goal of soybean breeding is to increase soybean oil content and yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that ubiquitination plays a key role in stress response and yield constitution [ 87 ]. In the UniProtKB database, 2429 ubiquitin-related proteins are predicted in soybean [ 85 ]. Ubiquitin plays a key role in regulating the resistance of soybean to Heterodera glycines , a soybean cyst nematode causal agent [ 84 ]; P. sojae , an infection that causes stem and root rot [ 86 ]; and heat shock [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global population is projected to reach 9 billion by 2050; with its continuous growth, it is important to consider how we can achieve food security [1]. Consequently, increasing crop yield has become a global scientific concern [2,3]. Soybean (Glycine max (L.) Merr.)…”
Section: Introductionmentioning
confidence: 99%